Intrinsic and extrinsic cues regulate the daily profile of mouse lateral habenula neuronal activity. (9th October 2014) - Sakhi, Kanwal; Wegner, Sven; Belle, Mino D. C.; Howarth, Michael; Delagrange, Philippe; Brown, Timothy M.; Piggins, Hugh D.
Abstract : Key points: Light input from the retina acts on clock neurones in the suprachiasmatic nuclei (SCN) and the intrinsic daily electrical output of these cell autonomous clocks coordinates circadian rhythms in the brain and body. Cells in the lateral habenula express clock genes and anatomical studies indicate that SCN output and retinal pathways terminate in this structure. Using a brain slice preparation isolating the lateral habenula from retinal and SCN inputs, we found mouse lateral habenula neurones exhibit a daily variation in their electrical properties that is dependent on a functional molecular clock. Prokineticin 2, a putative output signal of the SCN, changed lateral habenula neuronal activity through enhancing inhibitory signalling. In response to retinal illumination in vivo, lateral habenula neurones sluggishly altered their electrical activity. These studies indicate that mouse lateral habenula neurones possess intrinsic timekeeping capabilities and show for the first time that they are responsive to extrinsic SCN and retinal signals. Abstract: The epithalamic lateral habenula (LHb) is implicated as part of the mammalian brain's circadian system. Anatomical evidence suggests that the LHb receives extrinsic circadian timing cues from retinal ganglion cells and the master clock in the suprachiasmatic nuclei (SCN). Intriguingly, some LHb neurones contain the molecular circadian clock, but it is unclear if and how intrinsic and extrinsic circadian processes influence neuronal activity in the mouse LHb. Here, using an in vitro brain slice preparation isolating the LHb from the SCN, we show through whole‐cell patch‐clamp recordings that LHb neurones exhibit heterogeneity in their resting state, but the majority spontaneously fire action potentials (APs). Discharge rate of APs varied from low firing in the early day to higher firing later in the day and was absent in LHb brain slices prepared from Cry1 −/− Cry2 −/− mice that lack a functional molecular clock. Low amplitude circadian oscillations in the molecular circadian clock were also monitored in LHb brain slices, but were absent in Cry1 −/− Cry2 −/− LHb brain tissue. A putative neurochemical output signal of the SCN, prokineticin 2 (PK2), inhibited some LHb neurones by elevating the frequency of GABA release in the LHb. Using multi‐electrode recordings in vivo, we found that LHb neurones sluggishly respond to retinal illumination, suggesting that they receive such information through polysynaptic processes. In summary, our results show for the first time that intrinsic circadian signals are important for regulating LHb neuronal state, while the SCN‐derived signal PK2 is less influential. Moreover, we demonstrate that mouse LHb neurones have access to and can respond to visual input, but such signals are unlikely to be directly communicated to the LHb. Broadly, these findings raise the possibility that intrinsic circadian signals are likely to be influential in shaping LHb contributions to cognition and emotionality.